2021
DOI: 10.1007/s00441-021-03427-6
|View full text |Cite
|
Sign up to set email alerts
|

Do uterine PTGS2, PGFS, and PTGFR expression play a role in canine uterine inertia?

Abstract: The aetiology of primary uterine inertia (PUI), which is the most common cause of canine dystocia, is still not elucidated. Prostaglandins (PGs) play a crucial role in parturition. We hypothesized that the expression of prostaglandin endoperoxidase synthase 2 (PTGS2), PGF2α synthase (PGFS), and corresponding receptor (PTGFR) is altered in PUI. We investigated PTGS2, PGFS, and PTGFR mRNA expression, and PTGS2 and PGFS protein expression in interplacental (IP) and uteroplacental sites (UP) in bitches with PUI, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 66 publications
(144 reference statements)
2
31
0
1
Order By: Relevance
“…Similar changes in uterine mRNA expression of smooth muscle γ-actin and myosin between PUI and OD bitches [8], or in oxytocin receptor expression between dogs in labor with dystocia and undergoing elective CS [16] were found before, but not for uterine expression of prostaglandin-endoperoxidase synthase 2 and the PGF2α pathway [14]. These differences seen here may be due to abnormal labor signaling, or protracted or inadequate uterine response in PUI bitches.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Similar changes in uterine mRNA expression of smooth muscle γ-actin and myosin between PUI and OD bitches [8], or in oxytocin receptor expression between dogs in labor with dystocia and undergoing elective CS [16] were found before, but not for uterine expression of prostaglandin-endoperoxidase synthase 2 and the PGF2α pathway [14]. These differences seen here may be due to abnormal labor signaling, or protracted or inadequate uterine response in PUI bitches.…”
Section: Discussionsupporting
confidence: 65%
“…Recently, advances were made in identifying defects in the contractile properties of the uterus at the cellular and molecular level. Our group showed that bitches diagnosed with PUI had higher uterine mRNA expression levels of smooth muscle γ-actin and smooth muscle myosin than dogs in labor still showing strong contractions [8], while gene expression of members of the prostaglandin (PG) F2α and PGE pathway did not differ [14,15]. Changes in uterine oxytocin receptor expression also did not seem to be implicated in the development of PUI [16].…”
Section: Introductionmentioning
confidence: 93%
“…Despite the frequent occurrence of PUI in dogs and its severe consequences for maternal and offspring survival, the exact etiology is still unknown. Up to now, only few studies have investigated its pathophysiology from a molecular biology approach looking directly at the level of the uterus [ 16 , 17 , 32 , 45 , 46 ]. As both oxytocin and progesterone are crucial hormones during parturition, we hypothesized and identified altered expression of the respective receptors as potential causes for PUI.…”
Section: Discussionmentioning
confidence: 99%
“…The significantly higher OXTR mRNA expression (ratio) in IP samples obtained from PUI (and PUI-N) dams compared to OD might be a consequence of the absence of intracervical pressure due to the fact that no puppy had been born and, thus, having insufficient systemic OXT release, as previously postulated by Tamminen et al [ 32 ]. It is worth noting that comparison of the OD and PUI samples was shown to be suitable in previous studies to gain further insight into the pathophysiology of canine dystocia and specifically PUI [ 15 , 16 , 17 , 32 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation